2018
DOI: 10.1111/acps.12875
|View full text |Cite
|
Sign up to set email alerts
|

Association of intracortical myelin and cognitive function in bipolar I disorder

Abstract: This is the first study to show VM association with ICM in BD. ICM has been implicated in the integrity of neural connections and neural synchrony. VM dysfunction is one of the most replicated cognitive abnormalities in BD. Therefore, these results provide a novel mechanism for understanding cognitive dysfunction in BD, which can aid in the development of targeted therapeutics to improve cognitive outcomes in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Exploring whether increased ICM in PCC in people with AUD is related to neurocognitive performance is an important next step. Differences in DLPFC / Brodmann Area 46 have also been reported in previous studies with patients with bipolar disorder [25].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Exploring whether increased ICM in PCC in people with AUD is related to neurocognitive performance is an important next step. Differences in DLPFC / Brodmann Area 46 have also been reported in previous studies with patients with bipolar disorder [25].…”
Section: Discussionsupporting
confidence: 81%
“…Prior studies with clinical samples have also indicated significant ICM disruption in people with bipolar disorder [16,24,25], schizophrenia [31,32], and other major mental health disorders [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations